The absence of remotely triggered seismicity in Gujarat, NW India during the Nepal earthquake, 2015 - Dixit, Mayank; Bansal, Abhey Ram (Frontiers in Earth Science, 2023)
Gujarat in the Northwestern Deccan Volcanic Province of India is among the most seismically earthquake-prone. The region may be susceptible to remote dynamic triggering, especially the Kachchh region, which recently hosted the M w 7.7 Bhuj earthquake in 2001. Its aftershocks continue because it is critically stressed and contains nucleation points more frequently close to failure. From waveforms and catalog data, we examine whether remote dynamic triggering occurs following April 25, 2015, M w 7.8 Nepal mainshock in the Gujarat region, Northwestern India. The 2015 Nepal event perturbed the Gujarat region with a peak dynamic stress of ~53 kPa, much higher than the global lower limit of 1kPa. Due to the large magnitude and high peak dynamic stress, ideally, the 2015 mainshock should have resulted in the triggered seismicity in the study region. To study the remote dynamic triggering in detail, we also have examined the other recent regional large earthquakes with comparable peak dynamic stresses (>50 kPa), namely April 16, 2013, M w 7.7 Iran, September 24, 2013, M w 7.7 Pakistan, and October 26, 2015, M w 7.7 Afghanistan. Our result shows that despite their significant peak dynamic stress, there is no significant change in the local seismicity. The analysis suggests that the surface wave amplitude is not the only factor that governs the remote dynamic triggering. Our results also indicate that the faults were not critically stressed during the mainshock candidates in the study region.